The influence of technique and physical capacity on ball release speed in cricket fast-bowling. Issue 20 (18th October 2021) - Kiely, Nathan; Pickering Rodriguez, Libby; Watsford, Mark; Reddin, Thomas; Hardy, Sean; Duffield, Rob
ABSTRACT: This study examined the relationships between physical capacity, bowling technique and ball speed in 20 fast-bowlers. Technique factors correlated with ball speed were; bowling action duration (r = -0.639, p = 0.002), run-up velocity (r = 0.616, p = 0.004), back foot contact (BFC) time (r = -0.608, p = 0.004), front foot contact (FFC)-ball release (BR) duration (r = -0.602, p = 0.005), delivery stride phase acceleration (r = -0.582, p = 0.007), delivery stride duration (r = -0.547, p = 0.012), time of peak horizontal braking force (r = -0.538, p=0.014), peak pelvis COM velocity (BFC-BR) (r = 0.469, p = 0.037) and peak vertical GRF time (r = -0.461, p = 0.041). Physical capacities were; 10-30 m split (r = -0.554, p = 0.011), 30 m sprint (r = -0.482, p = 0.031) and IMTP (r = 0.471, p = 0.036). Stepwise regression showed bowling action duration and 10-30 m split explained 54% (p = 0.001) of ball speed variation. Ball speed was associated with faster run-ups, shorter BFC times and abrupt FFC GRF application. Coaches should also consider sprint speed and lower-body strength as important modifiable factors for fast-bowlers.